AUDIT SISTEM INFORMASI MANAJEMEN RUMAH SAKIT MENGGUNAKAN METODE FRAMEWORK 4.0 DI RUMAH SAKIT UMUM DAERAH WANGAYA - Wasita, Rai Riska Resty; Firsta Adnyana, Gabriel (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2025)
Background: Wangaya Regional General Hospital (RSUD) has utilized a hospital management information system (SIMRS) since 2013 to support every health service process in the hospital. In its implementation, several obstacles are still encountered that can hinder the objectives of SIMRS as well as obstacles in the preparation of recommendations for SIMRS development, resulting in management having difficulty in determining the direction and policies for SIMRS development. Objectives: To determine the level of maturity of the implementation and recommendations in the development of SIMRS in order to increase the effectiveness of achieving the mission of Wangaya Hospital, Denpasar City as a Regional Public Service Agency (BLUD). Methods: Quantitative descriptive research with a case study approach. A sample of seven SIMRS officers was obtained by total sampling. The data collection method was by observing the implementation of SIMRS and providing questionnaires referring to the maturity level based on the 4 COBIT 4 domains. Results: Based on the research results, the maturity level values ​​were obtained in the Planning and Organization, Acquisition and Implementation, Delivery and Support, and Monitoring and Evaluation domains with an average maturity level valu e of 3 (Defined Level). Conclusions: This shows that the SIMRS maturity level of Wangaya Hospital is generally at level 3 (Defined Level), while in general the SIMRS maturity level that Wangaya Hospital wants to achieve is at level 5 (Optimized Level). It is necessary to carry out governance that is aligned by creating SIMRS procedures and policies that are in accordance with the strategy of Wangaya Hospital, Denpasar to achieve the hospital's vision and mission.